2021
DOI: 10.1016/j.orcp.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity and diabetes mellitus in critically ill patients with SARS-CoV-2

Abstract: Purpose Evaluate the associations of obesity and diabetes with the risk of mortality in critically ill patients infected with SARS-CoV-2. Materials and methods This cohort study included 115 adult patients admitted to the ICU with SARS-CoV-2 pneumonia. Anthropometric variables and biochemical (C-reactive protein, ferritin, leukocyte, neutrophils, and fibrinogen) were measured. Multivariate logistic regression analyses were used to investigate the associations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A detailed description of the studies included in the two groups is provided in Data S1 12–194 . The literature search yielded a total of 826 citations.…”
Section: Data Extractionmentioning
confidence: 99%
“…A detailed description of the studies included in the two groups is provided in Data S1 12–194 . The literature search yielded a total of 826 citations.…”
Section: Data Extractionmentioning
confidence: 99%
“…Of the 35 studies selected for the methodological assessment using the Downs and Black scale [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], 1 study scored 6/17 [ 35 ], 3 scored 7/10 [ 36 , 37 , 38 ], 11 scored 8/17 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], 12 scored 9/17 [ 50 , 51 ,…”
Section: Resultsmentioning
confidence: 99%
“…Of the 35 studies selected for the methodological assessment using the Downs and Black scale , 1 study scored 6/17 [35], 3 scored 7/10 [36][37][38], 11 scored 8/17 [39][40][41][42][43][44][45][46][47][48][49], 12 scored 9/17 [50][51][52][53][54][55][56][57][58][59][60][61], 7 scored 10/17 [27][28][29][30][32][33][34], and 1 study scored 11/17 [31]. Only eight studies obtained 60% or more of the total scale score (17 points) [27][28][29][30][31][32][33][34]; therefore, they were selected to be analyzed in this systematic review (see Supplementary Table S1).…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…It has been reported that obesity significantly increases ORs for mortality in COVID-19 patients with hypertension or diabetes mellitus (DM) [192], and the OR reaches the peak in patients with hypertension, DM, and obesity [192,193]. Several independent research works show that obesity confers increased risk of adverse outcomes, including ICU admission, invasive mechanical ventilation, and in-hospital death, to COVID-19 patients with DM [194][195][196]. Holman et al [197] found that obesity only increases risk of COVID-19-related death in patients with DM type I, which is opposite to the report of Cariou et al [198].…”
Section: Comorbiditymentioning
confidence: 99%